To the question about trade of bobac in soviet and post-soviet periods - Grigoryeva, I.V.; Abukenova, V.S. (Fundamental and Experimental Biology, 2017)
In the article information on main objectives of production of groundhog, kinds that was obtained equally with a steppe marmot, and in places replaced production of a bobac with other species of groundhogs. According to the available data it is considered its number in various habitats, also distribution of a steppe groundhog in territories of the former Soviet Union is considered taking into account anthropogenic action on the places of the inhabiting of the steppe marmot for example: such as a pasture of cattle or virgin land development. We are affect the theme of active trade of marmot, that is a major factor, leading it to the decline, because of what hunting for a steppe groundhog was forbidden several times during existence of the Soviet Union, and in some territories of population of a bobac disappear completely, despite the introduced restrictions on trade. We draw conclusions about influence of trade on population of a baybak during the Soviet and Post-Soviet periods in territories of his habitation, and the impact of the development of virgin lands and pasture of large and small cattle.